2021
DOI: 10.1177/0022243721993816
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Ownership of (Borrowed) Money

Abstract: The current research introduces the concept of psychological ownership of borrowed money, a construct that represents how much consumers feel that borrowed money is their own. We observe both individual-level and contextual-level variation in the degree to which consumers feel psychological ownership of borrowed money, and variation on this dimension predicts willingness to borrow money for discretionary purchases. At an individual level, psychological ownership of borrowed money is distinct from other individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 49 publications
(48 reference statements)
0
31
0
Order By: Relevance
“…Discretionary borrowing Borrowed money is "money available for use by one entity that is owned by another" (Sharma et al 2021). Research on consumer borrowing suggests that consumers' willingness to borrow stems from consumer characteristics (e.g., age, attitude toward credit, income; Jiang, Su, and Zhu 2019;Kim and DeVaney 2001;Sharma, Tully, and Cryder 2021), psychological ownership (Sharma et al 2021), the underlying purchase (e.g., physical longevity of purchases, material versus experiential purchases; Bauer, Morwitz, and Nagengast 2021; Tully and Sharma 2018), and the terms of the loan (e.g., interest rates, credit limits, repayment options; Gross and Souleles 2002;Soman and Cheema 2002;Tully and Sharma 2018). Further research also demonstrates that psychological factors related to consumers' finances also impact borrowing decisions (Sharma et al 2021).…”
Section: Discretionary Spendingmentioning
confidence: 99%
“…Discretionary borrowing Borrowed money is "money available for use by one entity that is owned by another" (Sharma et al 2021). Research on consumer borrowing suggests that consumers' willingness to borrow stems from consumer characteristics (e.g., age, attitude toward credit, income; Jiang, Su, and Zhu 2019;Kim and DeVaney 2001;Sharma, Tully, and Cryder 2021), psychological ownership (Sharma et al 2021), the underlying purchase (e.g., physical longevity of purchases, material versus experiential purchases; Bauer, Morwitz, and Nagengast 2021; Tully and Sharma 2018), and the terms of the loan (e.g., interest rates, credit limits, repayment options; Gross and Souleles 2002;Soman and Cheema 2002;Tully and Sharma 2018). Further research also demonstrates that psychological factors related to consumers' finances also impact borrowing decisions (Sharma et al 2021).…”
Section: Discretionary Spendingmentioning
confidence: 99%
“…Our work adds to growing evidence that psychological ownership influences societal welfare. For example, recent research has shown that psychological ownership can impact consumer borrowing ( 12 ) and the stewardship of public goods ( 21 ). There are also interventions that may provide convergent evidence for the impact of psychological ownership in the healthcare space.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological ownership is a fundamental human perception ( 9 , 10 ) and refers to the perception that a target is “mine” ( 11 ). Although psychological ownership has primarily been studied with respect to people’s feelings toward organizations and products, recent research has demonstrated that people can experience psychological ownership toward monetary resources and that these perceptions can influence financial decisions ( 12 , 13 ). However, there have been seemingly no large-scale field investigations designed to directly examine whether psychological ownership impacts societal welfare, and the potential magnitude of its effects.…”
mentioning
confidence: 99%
“…Further, the perception of being financially abundant or constrained is a ubiquitous phenomenon that differentially influences a variety of consumer behavior. For example, perceived level of financial resources influences discretionary spending (De La Rosa & Tully, 2020 ; Sharma et al, 2021 ), choices (Sharma & Alter, 2012 ; Tully et al, 2015 ), and post-consumption behavior (Paley et al, 2019 ). Given the far-reaching consequences of perceived financial resources across various life domains, further understanding of how such perceptions influence purchase decisions and the factors that moderate such decisions are important areas of investigation.…”
Section: Introductionmentioning
confidence: 99%